2020
DOI: 10.5114/fn.2020.102435
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide mediates Wnt/β-catenin signalling pathway to reduce cerebral ischemia-reperfusion injury in rats

Abstract: Introduction: Triptolide, extracted from Chinese medicinal materials Tripterygium wilfordii Hook F (TwHF), has immunosuppressive, anti-inflammatory and anti-tumour effects. The purpose of this study was to examine whether triptolide has the neuroprotective effect on cerebral ischemia-reperfusion (I/R) injury and to explore its possible mechanism. Material and methods: The rat model of focal cerebral I/R was established by the suture-occluded method. The SD rats were randomly divided into five groups: sham oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Pan et al also reported the therapeutic effects of triptolide on MCAO. In their experimental results, triptolide could improve neurobehavioral scores, reduce brain damage, exert anti-inflammatory and antioxidant effects (reduce levels of malondialdehyde (MDA) and ROS, increase superoxide dismutase (SOD) level), and these effects were associated with inhibition of Wnt/β-catenin signaling pathway ( Pan and Xu, 2020 ). In addition, right unilateral common carotid artery occlusion (rUCCAO), which simulates chronic cerebral hypoperfusion, can also be used for cerebral ischemia related research ( Yoshizaki et al, 2008 ).…”
Section: Effects Of Triptolide and Celastrol On Brain And Spinal Cord...mentioning
confidence: 99%
“…Pan et al also reported the therapeutic effects of triptolide on MCAO. In their experimental results, triptolide could improve neurobehavioral scores, reduce brain damage, exert anti-inflammatory and antioxidant effects (reduce levels of malondialdehyde (MDA) and ROS, increase superoxide dismutase (SOD) level), and these effects were associated with inhibition of Wnt/β-catenin signaling pathway ( Pan and Xu, 2020 ). In addition, right unilateral common carotid artery occlusion (rUCCAO), which simulates chronic cerebral hypoperfusion, can also be used for cerebral ischemia related research ( Yoshizaki et al, 2008 ).…”
Section: Effects Of Triptolide and Celastrol On Brain And Spinal Cord...mentioning
confidence: 99%
“…Wnt/β-catenin pathway is abnormally activated in I/RI and exacerbates I/RI [ 20 22 ]. Therefore, this study speculates that circARAP1 may activate the Wnt/β-catenin pathway by affecting the miR-379-5p/KLF9 axis.…”
Section: Resultsmentioning
confidence: 99%
“…Wnt/β-catenin pathway plays a key role in cell growth, differentiation, migration, polarity and death [ 37 ]. Recently, the wnt/β-catenin pathway has been shown to be abnormally activated in I/RI [ 20 22 ]. The present study exhibited that circARAP1 activates the Wnt/β-catenin pathway by regulating the miR-379-5p/KLF9 axis to affect cardiomyocyte H/R injury and MI/RI in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the protein and mRNA expression of Wnt3a and β -catenin increased in the brain tissues from the model group at all three time points, which might be a built-in antidamage mechanism (Figures 4 and 5 ). Notably, no significant increases of TCF4 and cyclin D1 were observed, suggesting that the activation of the Wnt/ β -catenin pathway caused by cerebral IR injury was insufficient to protect brain tissues from cerebral IR injury [ 28 , 29 ]. After scalp electroacupuncture treatment, the mRNA and protein expression levels of Wnt3a and β -catenin rose in the infarct area of brain tissue and further resulted in cascade upregulation of TCF4 and cyclin D1 (Figures 4 and 5 ).…”
Section: Discussionmentioning
confidence: 99%